2016
DOI: 10.1111/cxo.12319
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant multiple myeloma spectrum diagnosis in a central retinal vein occlusion: a case report and review

Abstract: Multiple myeloma is a neoplastic plasma-cell disorder resulting from malignant plasma cells in the bone marrow. It can cause a hyperviscosity syndrome secondary to the paraproteinaemia associated with the disease. The increased hyperviscosity can lead to retinal vein occlusions and other ocular problems that may challenge clinicians. In patients with multiple myeloma and hypertension and/or diabetes mellitus, retinal changes appear similar and changes due to one disease or the other may be difficult to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Regarding the second limitation, retinal vasculature and choroidal vasculature are also affected by systemic hypertension. In eyes with retinal diseases 16 , 17 , such as diabetic retinopathy 21 23 , retinal vascular occlusion 24 , and epiretinal membrane disorders 18 , the retinal vasculature is expected to show changes that make the estimation of systemic hypertensive vascular changes difficult. OCTA cannot distinguish between the small-vessel and large-vessel layers of the choroidal vasculature and might generate an overlapped microvascular image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the second limitation, retinal vasculature and choroidal vasculature are also affected by systemic hypertension. In eyes with retinal diseases 16 , 17 , such as diabetic retinopathy 21 23 , retinal vascular occlusion 24 , and epiretinal membrane disorders 18 , the retinal vasculature is expected to show changes that make the estimation of systemic hypertensive vascular changes difficult. OCTA cannot distinguish between the small-vessel and large-vessel layers of the choroidal vasculature and might generate an overlapped microvascular image.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal vasculature and choroidal vasculature are affected by systemic hypertension, and are also Retinal and choroidal vasculature is expected to change with age 10 , 11 , axial length (AL) 12 , 13 , intraocular pressure (IOP) 14 , 15 , and many diseases 16 – 24 . Such as diabetic retinopathy, retinal vascular occlusion, and epiretinal membrane disorders, making the estimation of systemic hypertensive vascular changes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperviscosity syndrome is a common complication in patients with multiple myeloma [25]. This complication may correlate with disease survival [26] because of the prolonged half-life albumin-bound IgA. Previous reports suggested that hyperviscosity syndrome in multiple myeloma may be responsible for increased blood cells (erythrocytes, leukocytes, and platelets) and macromolecules (mainly immunoglobulins) in the blood [25].…”
Section: Discussionmentioning
confidence: 99%
“…CRVO is known to be associated with MM. In this context, CRVO mainly occurs due to hyperviscosity syndrome ( 8 ). In addition, various coagulation disorders can also trigger this complication ( 9 ).…”
Section: Discussionmentioning
confidence: 99%